An Allegory of the Political Influence of the Top 1% - Philippe De Donder; John E. Roemer (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study how rich shareholders can use their economic power to deregulate firms that they own, thus skewing the income distribution towards themselves. Agents differ in productivity and choose how much labor to supply. High productivity agents also own shares in the productive sector and thus earn capital income. All vote over a linear tax rate on (labor and capital) income whose proceeds are redistributed lump sum. Capital owners also lobby in order to ease the price cap imposed on the private firm. We solve analytically for the Kantian equilibrium of this lobbying game together with the majority voting equilibrium over the tax rate, and we perform simulations. We obtain numerically that, as the capital income distribution becomes more concentrated among the top productivity individuals, their increased lobbying effort generates efficiency as well as equity costs, with lower labor supply and lower average utility levels in society.
Keywords: D71; H31; 330; political economy; Kantian equilibrium; lobbying; regulatory capture